Understanding teacher emotional exhaustion: exploring the role of teaching motivation, perceived autonomy, and teacher–student relationships - Wang, Xiaoyu; Yang, Li; Chen, Kun; Zheng, Yanan (Frontiers in Psychology, 2024)
This research delves into the intricate web of factors impacting teacher emotional exhaustion within the educational setting. Drawing from a diverse sample of 680 teachers from 15 primary educational institutions located across various districts in Shanghai, China, this study investigates the interrelationships among teacher-student relationships, perceived autonomy, teaching motivation, and emotional exhaustion. The research explored these constructs by employing validated scales to measure emotional exhaustion, teacher-student relationships, perceived autonomy, and teaching motivation. Utilizing Structural Equation Modeling (SEM), the analyses revealed significant associations among the examined variables. Specifically, the results indicated strong correlations between positive teacher-student relationships, perceived autonomy, and higher teaching motivation, while also showcasing a negative relationship between these factors and emotional exhaustion. Moreover, the mediation analysis unveiled that teaching motivation significantly mediated the associations between teacher-student relationships, perceived autonomy, and emotional exhaustion, elucidating the intricate indirect effects. These findings underscore the multifaceted nature of these constructs and their collective impact on teacher wellbeing within educational contexts. The implications derived from this study accentuate the need for educational institutions to prioritize interventions that cultivate positive teacher-student relationships, establish autonomy-supportive environments, and foster intrinsic motivation among educators to mitigate emotional exhaustion and enhance teacher well-being.